Pengujian dan Validasi Sistem Kasir Berbasis Web Menggunakan Standar Pengujian ISO/IEC 29119 - Florida Virginia Luan; Leli Fatmasari; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The adoption of web-based cashier systems has become a common choice among small and medium-sized enterprises due to their ability to streamline transaction processes and simplify sales data management. Nevertheless, ensuring the quality of such software requires a structured testing and validation approach. This study focuses on applying the ISO/IEC 29119 international standard as a framework for testing a web-based cashier system. The research stages include test planning, test case design, test execution, and result evaluation in accordance with the standard. Findings indicate that the system meets functional, reliability, and usability requirements aligned with operational needs. Validation was conducted by comparing test outcomes with system specifications and business requirements, leading to the conclusion that the tested web-based cashier system is suitable for implementation. The application of ISO/IEC 29119 provides a systematic and consistent methodology for software testing, thereby enhancing confidence in the quality of the developed system.